Application of Wireless Sensor Network for the Monitoring Systems of Vessels - Kdouh, Hussein; Zaharia, Gheorghe; Brousseau, Christian; Farhat, Hanna; Grunfelder, Guy; Zein, Ghaïs El (IntechOpen, 2012)
None